Associations between TGF-β1 Levels and Markers of Hemolysis, Inflammation, and Tissue Remodeling in Pediatric Sickle Cell Patients. (15th March 2021) - Santiago, Rayra P.; Carvalho, Magda O. S.; Figueiredo, Camylla V. B.; Fiuza, Luciana M.; Oliveira, Rodrigo M.; Yahouédéhou, Sètondji C. M. A.; Nascimento, Valma M. L.; Lyra, Isa M.; Araujo-Santos, Théo; Luz, Nívea F.; Aleluia, Milena M.; Guarda, Caroline C.; et al.
Abstract : Transforming growth factor beta (TGF- β ) is a cytokine with important involvement in biological processes related to the pathogenesis of sickle cell disease (SCD), including endothelial and vascular dysfunction, inflammation, and hematopoietic homeostasis. This study is aimed at investigating associations between levels of TGF- β 1 and classical laboratory biomarkers and inflammatory mediators, as well as the tissue inhibitor of metalloproteases-1 (TIMP-1) and matrix metalloproteinase-9 (MMP-9), in pediatric patients (n = 123 ) with SCD in steady state: 84 with sickle cell anemia (HbSS) and 39 with hemoglobin SC disease (HbSC). A healthy control (HC) group of 59 individuals was also included. Hematological and biochemical analyses were carried out using electronic methods. TGF- β 1, TIMP-1, and MMP-9 plasma quantifications were performed by ELISA. TGF- β 1 plasma levels were higher in HbSS individuals than in HbSC and HC. In individuals with HbSS, TGF- β 1 levels were positively correlated with red blood cells, hemoglobin, hematocrit, platelets, and TIMP-1. In addition, HbSS individuals with TGF- β 1 levels above the median (≥72.29 ng/mL) also presented increased monocyte counts and decreased albumin levels. In patients with HbSC, TGF- β 1 levels were positively correlated with leukocytes, eosinophils, lymphocytes, monocytes, and platelets, as well as levels of TIMP-1, VLDL-C, triglycerides, heme, and AST. Additionally, HbSC individuals with TGF- β 1 levels above the median (≥47.80 ng/mL) presented increased leukocyte and platelet counts, as well as increased levels of triglycerides, VLDL-C, MMP-9, and TIMP-1, and decreased HDL-C. Our findings suggest that TGF- β 1 may play important roles in vascular remodeling, vasculopathy, angiogenesis, and inflammation in pediatric patients with SCD.